Effect of smoking status on lung function, patient-reported outcomes, and safety among patients with COPD treated with indacaterol/glycopyrrolate: Pooled analysis of the FLIGHT1 and FLIGHT2 studies. (August 2019) - Tashkin, Donald P.; Goodin, Thomas; Bowling, Alyssa; Price, Barry; Ozol-Godfrey, Ayca; Sharma, Sanjay; Sanjar, Shahin
Abstract: Background: Smoking continues to be a major risk factor for COPD and may impact the efficacy of COPD treatments, with guidelines supporting the crucial importance for current smokers of smoking cessation. A post-hoc analysis of the FLIGHT1 and FLIGHT2 studies assessed the impact of smoking status on the efficacy and safety of indacaterol/glycopyrrolate (IND/GLY) 27.5/15.6 μg twice daily versus its monocomponents or placebo in patients with COPD. Methods: This post-hoc analysis of pooled data from the replicate, 12-week, placebo-controlled FLIGHT1 and FLIGHT2 studies compared the efficacy and safety of IND/GLY with that of IND, GLY, and placebo in patients with moderate-to-severe COPD. Baseline data from 2038 patients were pooled and grouped by smoking status (52% were current smokers and 48% were ex-smokers). The effects of treatment on lung function, patient-reported outcomes (PROs), and safety were evaluated by baseline smoking status. Results: Treatment with IND/GLY resulted in significant improvements in lung function measurements compared with placebo, irrespective of smoking status. Improvements in St George's Respiratory Questionnaire and transition dyspnea index were significantly greater than placebo in both current and ex-smokers, whereas changes in COPD assessment test were significant only among current smokers. Improvements in lung function and PROs were greater with IND/GLY compared with its monocomponents in current and ex-smokers. The incidences of AEs and SAEs were similar between current and ex-smokers. Conclusions: IND/GLY demonstrated significant improvements in lung function and PROs, independent of baseline smoking status. The safety profile of IND/GLY did not differ between current and ex-smokers. Highlights: FLIGHT1 and FLIGHT2 were replicate 12-week trials of IND/GLY in patients with COPD. This post-hoc analysis assessed impact of smoking on IND/GLY efficacy and safety. Lung function improvement with IND/GLY was similar in current and ex-smokers. Improvements in some PROs with IND/GLY differed between current and ex-smokers. Safety profile of IND/GLY was not affected by smoking status at baseline.